Re-design of a guide bearing for pneumatic actuators and life tests comparison. (April 2016) - Ambu, Rita; Bertetto, Andrea Manuello; Mazza, Luigi
Abstract: The re-design at the front-head/guide-bearing interface of a linear pneumatic actuator is proposed in this paper. Design changes were performed by means of finite element analyses. Contact pressure and its redistribution at the rod-guide interface were assumed to be the "leading parameter" in this process to promote improvements of tribological behaviour, viz., reduction of guide-bearing wear and increase of cylinder life. Wear measurements and life tests made possible a comparison of pneumatic actuator life: these were modified on the basis of the various re-design solutions proposed. Therefore, a validation of the model׳s predicted conditions was possible. Highlights: Re-design of the rod guiding system of a pneumatic actuator by means of FE analysis. Contact pressure distribution used as a "key parameter" to promote wear reduction. Effectiveness of the design choices proved by life tests and wear analysis. Simulations and experiments as viable tools in guide bearings design evaluation.